Faktor-Faktor yang Mempengaruhi Terjadinya Anemia pada Remaja Putri - Yeni Indrawatiningsih; ST Aisjah Hamid; Erma Puspita Sari; Heru Listiono (Universitas Batanghari Jambi, 2021)
Anemia is a major health problem for people in the world, especially in developing countries, about 50-80% of anemia is caused by iron deficiency. The purpose of this study was to determine the factors that influence the occurrence of young women. This research is an analytical survey with a cross sectional research design, the study was conducted in May - June 2020 in the village of Sidomakmur, Gumawang Community Health Center, East OKU Regency, the population in this study were all young women recorded by village midwives in Sidomakmur Village, totaling 212 people. and the sample is some of the young women who take part in the Posyandu Youth in Sidomakmur Village, amounting to 98 people, through Proportional Random Sampling, univariate (proportion), bivariate (chi square test) and multivariate (logistic regression) analysis. The results of the analysis showed that adolescent education (p value: 0,000), parents' income (p value: 0.012) and adolescent nutritional status (p vaue: 0,000) had a significant relationship with the incidence of anemia in adolescent girls, while adolescent age (p value: 0.224). ) does not have a significant relationship with the incidence of anemia in adolescent girls, while the age of adolescents. Based on the final model of multivariate analysis, the variable that had the greatest influence on anemia status was the variable nutritional status. It is necessary to provide counseling to young women and improve the way of delivering information when young women conduct examinations on how to prevent anemia, both in the form of a good healthy lifestyle and how to maintain health for the growth and development of young women themselves.